How Firms are Responding and Adapting During COVID-19 and Recovery : Opportunities for Accelerated Inclusion in Emerging Markets - International Finance Corporation (International Finance Corporation, Washington, DC, 2021)
Coronavirus disease 2019 (COVID-19), which began as a health crisis in early 2020, has rapidly evolved to become an unprecedented economic crisis affecting global, national, and regional economies and billions of individuals around the world. This report analyzes the widespread implications of the crisis on industry sectors, businesses, individuals, families, and communities. It closely examines evidence and data from business sectors and segments of society that may face challenging paths to recovery, including the most vulnerable firms and individuals in emerging markets that are likely to experience continuing hardship and specific difficulties coping with the crisis. And it highlights opportunities for the private sector to respond, to support a vigorous recovery and to build back better. The first section of the report, chapters 1 to 5 addresses issues that cut across sectors, as well as ways the development community can join with the private sector to help impacted communities and sectors recover and rebuild. The second section, chapters 6 to 9 focus on sector-specific responses to the crisis. The final section, chapters 10 to 12 attends to gender inequities, how they have been aggravated by the crisis, and potentially effective remedies.